Composite microstructures and piezoelectric properties in tantalum substituted lead-free K0.5Na0.5Nb1-xTaxO3 ceramics. Issue 8 (1st June 2018) - Jean, F.; Schoenstein, F.; Zaghrioui, M.; Bah, M.; Marchet, P.; Bustillo, J.; Giovannelli, F.; Monot-Laffez, I.
Abstract: K0.5 Na0.5 Nb1-x Tax O3 (KNNT) (with x = 0.00, 0.05, 0.10, 0.20, 0.30, 0.50 and 1) ceramics are prepared by ball milling and two calcinations at 830 °C for 5 h. Subsequent sintering of centimeter size pellets, 1–2 mm thick, is studied using conventional and spark plasma sintering techniques with various conditions. X-Ray diffraction and Raman spectroscopy phase identification reveal orthorhombic to tetragonal phase transitions occurring at about x = 0.50, associated to chemical disorder. Scanning electron microscope observations and associated energy dispersive X-ray spectroscopy analysis reveal some composite aspect of the ceramics. Substitution of niobium by tantalum, corresponding to x increase, decreases significantly the grain size but also the densification of the ceramics sintered by conventional sintering, while, enhancement of the piezoelectric properties is observed for both sintering techniques. Thanks to parameters optimization of the spark plasma sintering process, temperature-time-pressure, significant improvement of the relative density over 96%, is obtained for all the compositions sintered between 920 and 960 °C, under 50 MPa, for 5–10 min with heating rates of 100 °C/min. High relative permittivity (εr = 1027), piezoelectric charge coefficient (d33 = 160 pC/N) and piezoelectric coupling factor (kp = 46%) are obtained in spark plasma sintered K0.5 Na0.5 Nb1-x Tax O3 composite ceramics, for x ranging between 0.10 and 0.30 and for some specific spark plasma sintering conditions. Thus, tantalum single element substitution on niobium site, combined with spark plasma sintering, is revealed to be a powerful combination for the optimization and the reliability of piezoelectric properties in KNN system.